2005
DOI: 10.1128/aem.71.2.904-911.2005
|View full text |Cite
|
Sign up to set email alerts
|

Unique Kinetic Properties of Phenol-Degrading Variovorax Strains Responsible for Efficient Trichloroethylene Degradation in a Chemostat Enrichment Culture

Abstract: ؊1 (enrichment 0.75) expressed the highest activity. Denaturing gradient gel electrophoresis of PCRamplified 16S rRNA gene fragments detected a Variovorax ribotype as the strongest band in enrichment 0.75; however, it was not a major ribotype in the other samples. Bacteria were isolated from enrichment 0.75 by direct plating, and their 16S rRNA genes and genes encoding the largest subunit of phenol hydroxylase (LmPHs) were analyzed. Among the bacteria isolated, several strains were affiliated with the genus Va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 40 publications
5
50
0
1
Order By: Relevance
“…Recently, it was found that biological processes might be linked with some specific dominant microbial populations [11,20,28]. Therefore, some dominant bacterial species were assumed to play an important role in maintaining the physical structure of aerobic granules and degrading pollutants [15,17].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was found that biological processes might be linked with some specific dominant microbial populations [11,20,28]. Therefore, some dominant bacterial species were assumed to play an important role in maintaining the physical structure of aerobic granules and degrading pollutants [15,17].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these bacterial genera have been cited in the literature in relation to the biodegradation of different environmental pollutants, like polycyclic aromatic hydrocarbons (PAHs) [8,22,23,45], trichloroethylene [16], aniline [2], dichloromethane [25], alkylbenzenesulfonates [37], and various pesticides [3,4,21,31,33,39]. However, apart from Stenotrophomonas sp.…”
Section: Total and Culturable Bacterial Diversity In Tnt-contaminatedmentioning
confidence: 98%
“…After electrophoresis, the gel was stained with SYBR Green I (Molecular Probes) for 30 min following the manufacturer's instructions. The nucleotide sequences of DGGE bands were determined as described previously (Futamata et al, 2005, Yoshida et al, 2005.…”
Section: Pcr-dggementioning
confidence: 99%
“…A number of laboratory studies have demonstrated that TCE is transformed cometabolically by aliphatic and aromatic hydrocarbondegrading bacteria under aerobic conditions (Ensley, 1991;Semprini, 1997;Futamata et al, 2005), while PCE is not transformed under aerobic conditions. However, PCE is reductively dechlorinated under anaerobic conditions by certain kinds of anaerobic bacteria (Smidt and de Vos, 2004;Futamata and Hiraishi, 2007).…”
Section: Introductionmentioning
confidence: 99%